Internationalization: Choosing The Right Entry Mode: Lessons From Ebay’s Strategy In China - Onyeka Uche Ofili (European Scientific Journal, ESJ, 2016)
This paper considers the motivations for businesses to expand to other countries using the entry of eBay into China as a case study. It observed that eBay adopted the wrong entry mode by acquiring 100 percent of EachNet. The company would have performed better if it had adopted the joint venture approach with minority stake as it later did with Tom Online or if it had only retained minority stake, as was the case when it acquired 33 percent of EachNet. It was discovered that the various entry modes have their pros and cons depending on the peculiarity of the host market. This paper therefore, recommends that in entering a new market, companies should ensure to have a proper understanding of the local business dynamics before settling for any entry strategy.